Relationship between Urinary Alzheimer-Associated Neuronal Thread Protein and Apolipoprotein Epsilon 4 Allele in the Cognitively Normal Population - Yuxia Li; Meimei Kang; Can Sheng; Guanqun Chen; Taoran Li; Jun Wang; Yanning Cai; Rong Wang; Ying Han (Neural Plasticity)
We investigated the relationship between urinary Alzheimer-associated neuronal thread protein (AD7c-NTP) levels and apolipoprotein epsilon 4 (ApoE ɛ4) alleles, as well as other factors that cause cognitive decline, in the cognitively normal population. We recruited 329 cognitively normal right-handed Han Chinese subjects who completed ApoE gene testing and urinary AD7c-NTP testing. There was no significant difference in urinary AD7c-NTP levels between the normal control and subjective cognitive decline groups. Urinary AD7c-NTP levels were significantly higher in subjects with ApoE ɛ3/4 and 4/4 [0.6074 (0.6541) ng/mL] than in subjects without ApoE ɛ4 [0.4368 (0.3392) ng/mL and 0.5287 (0.3656) ng/mL], and urinary AD7c-NTP levels positively correlated with ApoE genotype grade (r=0.165, p=0.003). There were significant differences in urinary AD7c-NTP levels between subjects with and without a history of coronary heart disease or diabetes. Urinary AD7c-NTP levels were not related to years of education, nature of work, family history of dementia, a history of hypertension, stroke, anemia, or thyroid dysfunction. Urinary AD7c-NTP levels were positively correlated with ApoE grade in the cognitively normal population. The relationship between risk factors of cognitive decline and urinary AD7c-NTP levels provides a new way for us to understand AD and urinary AD7c-NTP.